Whole-genome sequencing: a perspective on sensing bacterial risk for food safety. (October 2022) - Zhang, Runrun; Yang, Tian; Zhang, Qiyi; Liu, Donghong; Elhadidy, Mohamed; Ding, Tian
Abstract : Pathogenic bacteria are one of the leading causes of foodborne outbreaks that need to be kept under stringent and constant surveillance. The current surveillance programs for microbial food safety are facing new challenges, such as the need for rapid and high-throughput subtyping, need for antimicrobial profiling, need for accurate source tracing, and need for delineation of transmission routes. Whole-genome sequencing (WGS), as a cutting-edge analytical tool, can reveal the comprehensive genomic information of a microorganism, that enables the precise identification and characterization of foodborne pathogens. The applications of WGS in food safety are renewing the current surveillance programs. This review summarizes the latest attempts of WGS in microbial food safety and discusses the potential of this technology to respond to future food-safety challenges. Highlights: Future food-safety surveillance program can identify the microbial contamination agents and track the contamination sources rapidly. WGS coupled with bioinformatic algrithoms can identify and characterize foodborne pathogens precisely. The applications of next-generation sequencing techniques might prevent foodborne outbreaks and associated problems.